2005
DOI: 10.1051/0004-6361:20042198
|View full text |Cite
|
Sign up to set email alerts
|

New distances of unresolved dwarf elliptical galaxies in the vicinity of the Local Group

Abstract: Abstract. We present Surface Brightness Fluctuation distances of nine early-type dwarf galaxies and the S0 galaxy NGC 4150 in the Local Volume based on deep B-and R-band CCD images obtained with the 2.56 m Nordic Optical Telescope. Typically, six stellar fields at various galactocentric distances have been chosen for each galaxy as appropriately free of foreground stars and other contaminants, and Fourier analysed to determine the distances, which are found to lie in the range of 3 to 16 Mpc. The SBF method is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 40 publications
3
34
0
Order By: Relevance
“…Another means to measure distances of galaxies is the surface brightness fluctuation method (SBF; Tonry & Schneider 1988). This method was successfully tested for earlytype dwarfs by Jerjen et al (2000b) and used to measure distances to five dE galaxies in the Centaurus group and many more in the Local Volume (Jerjen et al 2001;Rekola et al 2005). The minimum exposure time required for the SBF method to work can be calculate using equation (1) in Dunn & Jerjen (2006).…”
Section: Centaurus Group Membershipmentioning
confidence: 99%
“…Another means to measure distances of galaxies is the surface brightness fluctuation method (SBF; Tonry & Schneider 1988). This method was successfully tested for earlytype dwarfs by Jerjen et al (2000b) and used to measure distances to five dE galaxies in the Centaurus group and many more in the Local Volume (Jerjen et al 2001;Rekola et al 2005). The minimum exposure time required for the SBF method to work can be calculate using equation (1) in Dunn & Jerjen (2006).…”
Section: Centaurus Group Membershipmentioning
confidence: 99%
“…Tonry et al 1989Tonry et al , 1994 but was found to work equally well with dwarf elliptical (dE) galaxies (e.g. Jerjen et al 1998, 2000, 2001, 2004, and Rekola et al 2005. As dE galaxies are by far the most numerous galaxy type at the current cosmological epoch, the SBF method in combination with wide-field CCD imaging offers the opportunity for the first time to spatially locate dEs in vast numbers and thereby to map in 3D the densest environments of the local Universe (for first results see contributions by Côté et al, Jerjen, Jordan et al, and Rekola et al in this volume).…”
Section: The Sbf Methods In a Nutshellmentioning
confidence: 99%
“…A SBF distance can be determined when the S/N is approximately 0.5, (see Fig. 8 in Rekola et al 2005), but that depends largely on the image quality i.e. seeing.…”
Section: Analysis Prerequisitesmentioning
confidence: 99%
“…The corresponding distances are 3.6 Mpc and 3.7 Mpc, respectively. Rekola et al (2005) has obtained distance moduli of 27.61 ± 0.17 (D = 3.3 Mpc) for KDG 61 and 27.74 ± 0.18 (3.5 Mpc) for KDG 64 using surface brightness fluctuation (SBF) method based on Band R-band images obtained with the Nordic Optical Telescope. Both measurements give consistent distances for our galaxies although the SBF measurements seem to give a little shorter scale.…”
Section: Distance Determinationmentioning
confidence: 99%